Opioid modulation of hypothalamic catecholaminergic neurotransmission and the pre-ovulatory LH surge in the rat - Yilmaz, Bayram; Gilmore, Desmond P. (Maghira and Maas Publications, 1999)
We have investigated the inter-relationship between the opioid and catecholaminergic systems in the control of LH secretion, and the involvement of ?- and ?-opioid subtypes in this process. Conscious female rats were intraperitoneally injected with either ?- (diamorphine) or ?-opioid agonists (U-50488H) alone or with their respective antagonists (naloxone and MR2266) before the critical period on pro-estrus. Hypothalamic catecholamine and plasma LH levels were determined by HPLC-ECD and RIA, respectively. Both ?- and ?-agonists significantly decreased concentrations of noradrenaline and its metabolite (DHPG) in all the hypothalamic regions examined concomitant with inhibition of the LH surge. Dopamine levels were selectively reduced only by the ?-agonist in the MPOA. The inhibitory effects of both opioid agonists were mostly reversed following their co-administration with naloxone and MR2266 (except the ?-antagonist on LH). These results indicate that both the ?- and ?-opioid subtypes may be involved in the inhibition of the LH surge by altering the hypothalamic noradrenaline content.
Keywords: Catecholamines; HPLC-ECD; LH surge; Opioid receptors